Settlers of Unassigned Lands - McLeod, Charles (21St Century Prose, 2015)
In these seven stories spanning the Midwest to California, Charles McLeod brings us characters estranged from their homelands and locked in conflict with their past and present selves. In "How to Start Your Own Midwestern Ghost Town," an unnamed narrator hatches a plan to capitalize on rural decay. A porn star trying to transition to the mainstream does an interview with a German reporter in "The Subject of Our First Issue Is Art." In the title story, a closeted heroin dealer follows a ghostly girl into an Oakland graveyard. And in "Rancho Brava," the conductor of a focus group about corporate salsa keeps getting interrupted by visitors from the Old West. Alternating between the comic, the tragic, and the neurotic-and often all three at once-McLeod's second collection transports readers from the American mainstream to the dark edges of cities and the heartland's lost, forgotten towns, into the lives of people trying to decipher if they can escape their pasts, and at what cost.